Understanding Revenue Administration : Results from the Second Survey of the Revenue Administration - Cleary, Duncan (Washington, D.C. : International Monetary Fund, 2017)
This paper presents the results of the second round of the Revenue Administration Fiscal Information Tool (RA-FIT) country survey in an aggregated manner for all respondents and by income group. Notwithstanding regional biases and some data quality issues with the sample, broad insights and trends are discernible from the data, and the results form part of an evolving series that will continue to develop and grow with the International Survey On Revenue Administration (ISORA), the successor survey to RA-FIT conducted by the IMF in collaboration with the Inter-American Center of Tax Administrations (CIAT), the Intra-European Organisation of Tax Administration (IOTA), and the Organisation for Economic Co-operation and Development (OECD). This paper expands on a previous one, which covered the first round of RA-FIT (Lemgruber and others 2015),1 and aims to allow countries to access information about key measures in revenue administration. Unlike the first paper, this one does not cover issues specific to customs administration but focuses rather on tax administration data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet